ANALYSE MORPHOLOGIQUE DES BIONYMES EN TOPOKE C53, LOKELE C55 ET OLOMBO C54 - Liwila, Nicolas MOMBAYA (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2021)
In this onomasiological approch, however, the main question is to find out in which lexical stratégies the contemplated linguistic communities disposed in oder to name plants and animals in their habitat. The purpose is to clear the morphosyntaxcical mecanism of lexical formation and so different lexical stuctures of these bionyms (a bantu bionym, as other name, is therefore the summary of a preffix and nomal theme, which may be simple or copound) and to clarify the different sources of lexical acquisition.